Multi-Functional Spatiotemporal Evolution of Cultivated Land and Its Driving Mechanisms in Poyang Lake Plain - Zhang Yujia; Cai Haisheng; Zhang Xueling; Chen Liting; He Qinggang (Shuitu baochi tongbao)
[Objective] The spatial and temporal evolution patterns and driving mechanisms of multifunctional cropland were analyzed in order to provide support for ensuring food security and promoting the coordinated development of regional multifunctional cropland along with socio-economic development. [Methods] The entropy power method, hierarchical analysis method, comprehensive index method, GIS spatial visualization analysis, and geographic probe were used in this study. [Results] ① The comprehensive function of arable land in each county of Poyang Lake p lain generally increased from 2000 to 2020, and was significantly influenced by socio-economic development level. Specifically, improvement of the comprehensive function of arable land was given priority to areas with faster socio-economic development, such as Nanchang County, Anyi County, and other areas around Nanchang City. ② Different trends of multi-functional changes were observed for arable land in Poyang Lake plain during the 20 years of the study. Production and landscape aesthetic functions showed a growing trend, while ecological maintenance and social security functions show a decreasing trend. These patterns indicated that even though the production function of arable land in Poyang Lake plain improved, it was difficult to guarantee the growing food and economic demand, while the rapid development of secondary and tertiary industries gradually decreased the proportion of economic contribution that arable land can provide. ③ The multi-functional development level of arable land in Poyang Lake plain was influenced by both social and natural factors. The social factors could be regulated by policies such as improving the basic conditions of agricultural production, guaranteeing the minimum income of rural residents, and improving the medical welfare standard of rural residents, while the natural environment requires human intervention to protect and restore the ecological environment. [Conclusion] A variety of factors jointly influenced the level of multifunctional development of arable land in Poyang Lake plain, and the rational formulation of policies related to the protection and utilization of arable land and the protection of rural residents’ living standards that have a facilitating effect on improving the level of multifunctional development of arable land.